Deception and Distress - Kaebnick, Gregory E. (The Hastings Center report, 2023)
In the lead article in the January-February 2023 issue of the Hastings Center Report, Abram Brummett and Erica Salter provide a conceptual framework to help physicians think through the ethics of deceiving a patient or someone closely connected to the patient. Brummett and Salter identify four main ethical features of any act of clinical deception and elaborate on how, in a given case, these features together influence the degree to which a deception could be justified. A second article in this issue presents an ethnographic study of the effect of the Covid-19 pandemic on critical care workers in an intensive care unit. The authors describe a level and form of moral distress that, they argue, goes beyond what the term "moral distress" captures. The authors offer "distressed work" to better mark the broad consequences for care workers’ roles, occupations, and vocations.